Diagnosis of Pancreatic Neuroendocrine Tumors - Dong Wook Lee; Michelle Kang Kim; Ho Gak Kim (Korean Society of Gastrointestinal Endoscopy, 2017)
Pancreatic neuroendocrine tumors (PNETs) are relatively rare; however, the incidence has increased over the last few decades. They are classified as functional or non-functional tumors according to the presence of associated clinical symptoms. The majority are non-functional tumors. For classification and staging, the World Health Organization 2010 classification system is the most commonly accepted. Chromogranin A is the most sensitive marker but has insufficient specificity. In general, PNETs are hypervascular tumors, and multiphasic contrast-enhanced computed tomography is considered the first choice for imaging study. Multiphasic magnetic resonance imaging can detect PNETs smaller than 2 cm and small liver metastasis compared with other modalities. Somatostatin receptor scintigraphy is often used in cases where functional PNETs are suspected. Positron emission tomography (PET) scan with 18F-fluorodeoxyglucose cannot visualize PNETs, but PET with 68-Ga DOTATATE can. Endoscopic ultrasonography can characterize smaller PNETs using contrast and confirm histology through fine needle aspiration or biopsy. In this article, we review the characteristics of grading systems and diagnostic modalities commonly used for PNETs.